1982
DOI: 10.1680/geot.1982.32.1.9
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of anchor plates in clay

Abstract: The undrained behaviour of anchor plates with a vertical or horizontal axis, resting in a saturated clay, is examined. Theoretical consideration is given to the effects of anchor embedment, layer depth, overburden pressure and breakaway condition as well as anchor roughness, thickness and shape. The influence of these parameters on the failure mechanism and the anchor capacity is discussed. It is shown that in many cases ultimate collapse is preceded by significant anchor displacement and a definition of failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
94
2
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 225 publications
(103 citation statements)
references
References 17 publications
5
94
2
2
Order By: Relevance
“…I. Numerical solutions developed by Rowe and Davis (1982) for cohesive soils can be used to evaluate the ultimate ' " ground surface…”
Section: Analytical Soil-pipeline Interaction: Transverse Movementmentioning
confidence: 99%
See 4 more Smart Citations
“…I. Numerical solutions developed by Rowe and Davis (1982) for cohesive soils can be used to evaluate the ultimate ' " ground surface…”
Section: Analytical Soil-pipeline Interaction: Transverse Movementmentioning
confidence: 99%
“…Rowe and Davis (1982) showed that the ultimate soil resistance is dependent on the embedment depth and the degree of bonding between the back of the pipeline and the soil. Figure 3 shows the solutions developed by Rowe and Davis (1982).…”
Section: Analytical Soil-pipeline Interaction: Transverse Movementmentioning
confidence: 99%
See 3 more Smart Citations